Pengembangan teknologi asistif aplikasi “I WANT…” untuk anak hambatan intelektual - Zudeta, Effran; Annisa; Marsyah, Ulfy; Khori Ulni, Elvira (Literal: Disability Studies Journal, 2025)
The high-tech Android-based application titled “I WANT..” as an assistive technology is expected to help children with intellectual disabilities convey their wishes to teachers and families, while evaluating its effectiveness in improving nonverbal communication and reducing the frequency of tantrums. This study utilized ADDIE model to develop the application. The application is designed using an approach that involves teachers, parents, and a student with intellectual disabillity (MA) in every stage of the design. The application displays daily activity icons (eating, drinking, studying, etc.) which when selected produce sound output. The “IWANT..” application is expected to be effective as a high-tech assistive technology in improving communication and reducing tantrum behavior in students with intellectual disabilities. This Android technology design can be expected to be used as a model for similar interventions in other special needs populations.